Efforts to Improve Cooperation Skills of 5-6 Year-Old Children Through Ball Relay Games - Karima Karima; Hilda Zahra Lubis (JURNAL TILA ( Tarbiyah Islamiyah Lil Athfaal ), 2026)
This study was motivated by the low level of cooperation skills among children aged 5–6 years at RA Amal Ikhlas, as reflected in their difficulties in sharing tasks, taking turns, helping peers, and following group rules during learning activities. The study aimed to improve children's cooperation skills through the implementation of a modified ball relay game incorporating a hula hoop tunnel obstacle. This research employed Classroom Action Research (CAR) using the Kemmis and McTaggart model, consisting of planning, action, observation, and reflection conducted over two cycles. The participants were 14 children aged 5–6 years. Data were collected through observation and documentation and analyzed using descriptive qualitative and quantitative techniques. The findings revealed that the modified ball relay game effectively improved children's cooperation skills. The average cooperation score increased from 41.00% in the pre-cycle to 65.70% in Cycle I and further improved to 83.55% in Cycle II. By the end of the study, 92.86% of the children had reached the categories of Developing as Expected (BSH) and Very Well Developed (BSB). Improvements were observed in children's ability to cooperate, communicate, take turns, share responsibilities, follow rules, and help peers during group activities. It can be concluded that the modified ball relay game is an effective, engaging, and innovative learning strategy for enhancing cooperation skills among children aged 5–6 years.